Evaluation of Protein Kinase C Inhibition of some Benzofuro[3,2-d]pyrimidine Derivatives - Thi Van Anh, Tran; Thanh Hoa, Ha; Quoc Tuan, Pham; Thi Sau, Ngo; Mai Huong, Do; Van Thang, Nguyen; Van Thao, Tran; Thanh Hai, Nguyen; Viet Hung, Dao (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Abstract: Treatment of fungal infections is very difficult because of the limited therapeutic arsenal and the emergence of resistance to the two major antifungal classes: azoles and echinocandins. Consequently, finding new targets and new therapeutic strategies is a priority. The protein kinase Pkc1 of Candida albicans ( Ca Pkc1), one of the key proteins involved in MAPK pathways, is described as a regulator of cell wall integrity during growth, morphogenesis, and response to cell wall stress. Therefore, the discovery of Ca Pkc1 inhibitory molecules can open up new and promising prospects in the development of new antifungal drugs that inhibit Ca Pkc1. In this study, we evaluated the Ca Pkc1 inhibitory activity of three benzofuro[3,2- d ]pyrimidine derivatives at three different concentrations of 50 µM, 100 µM, and 150 µM. A concentration of 100 μM was optimal for Ca Pkc1 inhibitory activity with all three benzofuro[3,2- d ]pyrimidine derivatives. Keywords: Benzofuro[3,2- d ]pyrimidine, Ca Pkc1, Candida albicans , antifungal activity.